2019
DOI: 10.3390/ijms20236105
|View full text |Cite
|
Sign up to set email alerts
|

Human Synovia Contains Trefoil Factor Family (TFF) Peptides 1–3 Although Synovial Membrane Only Produces TFF3: Implications in Osteoarthritis and Rheumatoid Arthritis

Abstract: Objective: Trefoil factor family peptide 3 (TFF3) has been shown to support catabolic functions in cases of osteoarthritis (OA). As in joint physiology and diseases such as OA, the synovial membrane (SM) of the joint capsule also plays a central role. We analyze the ability of SM to produce TFF compare healthy SM and its secretion product synovial fluid (SF) with SM and SF from patients suffering from OA or rheumatoid arthritis (RA). Methods: Real-time PCR and ELISA were used to measure the expression of TFFs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…Trefoil factors (TFFs) are a group of stable polypeptides with a molecular weight of 6–12 kDa, which are secreted by mucus-secreting cells of the mammalian gastrointestinal epithelium. TFF1, TFF2, and TFF3 are essential components of the TFF family [ 20 , 21 , 22 , 23 ], which are expressed in the gastrointestinal tract and are present in virtually all mucous membrane [ 21 , 23 ]. Based on the special three-loop leaf-like structure, TFFs were extremely stable towards proteolytic digestion (including acid and heat degradation) [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Trefoil factors (TFFs) are a group of stable polypeptides with a molecular weight of 6–12 kDa, which are secreted by mucus-secreting cells of the mammalian gastrointestinal epithelium. TFF1, TFF2, and TFF3 are essential components of the TFF family [ 20 , 21 , 22 , 23 ], which are expressed in the gastrointestinal tract and are present in virtually all mucous membrane [ 21 , 23 ]. Based on the special three-loop leaf-like structure, TFFs were extremely stable towards proteolytic digestion (including acid and heat degradation) [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Based on the special three-loop leaf-like structure, TFFs were extremely stable towards proteolytic digestion (including acid and heat degradation) [ 24 , 25 ]. Nowadays, TFF1 was confirmed to be necessary for the pathogenesis of breast cancer, and TFF2 was associated with the inflammatory bowel disease [ 22 , 23 , 26 ]. Although it has been shown that TFF1 and TFF2 are downregulated in primary gastric cancer [ 27 ], the interaction between TFFs and DNA methylation in gastric cancer remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…For the future, more sophisticated strategies can be expected, which could allow numerous novel medical applications for TFF peptides; possible fields would be inflammation-induced fibrosis, rheumatoid arthritis, or neurodegeneration. For example, TFF2 regulates airway remodeling [ 187 ], reversed airway fibrosis [ 108 ], and is upregulated in the synovial fluid of rheumatoid arthritis samples [ 188 ], whereas TFF3 is associated with neurodegeneration [ 189 ]. However, there are many open questions currently and there is a strong necessity for further research before application in clinics can be considered, e.g., for the treatment of various immune mediated inflammatory disorders.…”
Section: Conclusion and Medical Perspectivesmentioning
confidence: 99%
“…Trefoil factors (TFFs) is a group of stable polypeptides with a molecular weight of 6-12 kDa, which is secreted by mucus-secreting cells of mammalian gastrointestinal epithelium. TFF1, TFF2, and TFF3 are essential components of the TFF family [20][21][22][23], which are expressed in the gastrointestinal tract and are present in virtually all mucous membrane [21,23]. Based on the special 3 loop leaf-like structure, TFFs were extremely stable towards proteolytic digestion (including acid and heat degradation) [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, TFF1 was confirmed to be necessary in the pathogenesis of breast cancer, and TFF2 was associated with the inflammatory bowel disease [22,23,26]. Although it has been shown that TFF1 and TFF2 are downregulated in primary gastric cancer [27], the interaction between TFFs and DNA methylation in gastric cancer remains unknown.…”
Section: Introductionmentioning
confidence: 99%